Chemotherapy plus lenalidomide versus autologous transplantation, followed by lenalidomide plus prednisone versus lenalidomide maintenance, in patients with multiple myeloma: a randomised, multicentre, phase 3 trial - Gay, Francesca; Oliva, Stefania; Petrucci, Maria Teresa; Conticello, Concetta; Catalano, Lucio; Corradini, Paolo; Siniscalchi, Agostina; Magarotto, Valeria; Pour, Luděk; Carella, Angelo Michele; Malfitano, Alessandra; Petrò, Daniela; et al. (Lancet oncology, 2015)
BACKGROUND: High-dose melphalan plus autologous stem-cell transplantation (ASCT) is the standard approach in transplant-eligible patients with newly diagnosed myeloma. Our aims were to compare consolidation with high-dose melphalan plus ASCT versus chemotherapy (cyclophosphamide and dexamethasone) plus lenalidomide, and maintenance with lenalidomide plus prednisone versus lenalidomide alone. METHODS: We did an open-label, randomised, multicentre, phase 3 study at 59 centres in Australia, Czech Republic, and Italy. We enrolled transplant-eligible patients with newly diagnosed myeloma aged 65 years or younger. Patients received a common induction with four 28-day cycles of lenalidomide (25 mg, days 1-21) and dexamethasone (40 mg, days 1, 8, 15, and 22) and subsequent chemotherapy with cyclophosphamide (3 g/m(2)) followed by granulocyte colony-stimulating factor for stem-cell mobilisation and collection. Using a 2 × 2 partial factorial design, we randomised patients to consolidation with either chemotherapy plus lenalidomide (six cycles of cyclophosphamide [300 mg/m(2), days 1, 8, and 15], dexamethasone [40 mg, days 1, 8, 15, and 22], and lenalidomide [25 mg, days 1-21]) or two courses of high-dose melphalan (200 mg/m(2)) and ASCT. We also randomised patients to maintenance with lenalidomide (10 mg, days 1-21) plus prednisone (50 mg, every other day) or lenalidomide alone. A simple randomisation sequence was used to assign patients at enrolment into one of the four groups (1:1:1:1 ratio), but the treatment allocation was disclosed only when the patient reached the end of the induction and confirmed their eligibility for consolidation. Both the patient and the treating clinician did not know the consolidation and maintenance arm until that time. The primary endpoint was progression-free survival assessed by intention-to-treat. The trial is ongoing and some patients are still receiving maintenance. This study is registered at ClinicalTrials.gov, number NCT01091831. FINDINGS: 389 patients were enrolled between July 6, 2009, and May 6, 2011, with 256 eligible for consolidation (127 high-dose melphalan and ASCT and 129 chemotherapy plus lenalidomide) and 223 eligible for maintenance (117 lenalidomide plus prednisone and 106 lenalidomide alone). Median follow-up was 52·0 months (IQR 30·4-57·6). Progression-free survival during consolidation was significantly shorter with chemotherapy plus lenalidomide compared with high-dose melphalan and ASCT (median 28·6 months [95% CI 20·6-36·7] vs 43·3 months [33·2-52·2]; hazard ratio [HR] for the first 24 months 2·51, 95% CI 1·60-3·94; p<0·0001). Progression-free survival did not differ between maintenance treatments (median 37·5 months [95% CI 27·8-not evaluable] with lenalidomide plus prednisone vs 28·5 months [22·5-46·5] with lenalidomide alone; HR 0·84, 95% CI 0·59-1·20; p=0·34). Fewer grade 3 or 4 adverse events were recorded with chemotherapy plus lenalidomide than with high-dose melphalan and ASCT; the most frequent were haematological (34 [26%] of 129 patients vs 107 [84%] of 127 patients), gastrointestinal (six [5%] vs 25 [20%]), and infection (seven [5%] vs 24 [19%]). Haematological serious adverse events were reported in two (2%) patients assigned chemotherapy plus lenalidomide and no patients allocated high-dose melphalan and ASCT. Non-haematological serious adverse events were reported in 13 (10%) patients assigned chemotherapy plus lenalidomide and nine (7%) allocated high-dose melphalan and ASCT. During maintenance, adverse events did not differ between groups. The most frequent grade 3 or 4 adverse events were neutropenia (nine [8%] of 117 patients assigned lenalidomide plus prednisone vs 14 [13%] of 106 allocated lenalidomide alone), infection (eight [8%] vs five [5%]), and systemic toxicities (seven [6%] vs two [2%]). Non-haematological serious adverse events were reported in 13 (11%) patients assigned lenalidomide plus prednisone versus ten (9%) allocated lenalidomide alone. Four patients died because of adverse events, three from infections (two during induction and one during consolidation) and one because of cardiac toxic effects. INTERPRETATION: Consolidation with high-dose melphalan and ASCT remains the preferred option in transplant-eligible patients with multiple myeloma, despite a better toxicity profile with chemotherapy plus lenalidomide. FUNDING: Celgene.
Keywords: Australia; Thalidomide; časové faktory; senioři; transplantace hematopoetických kmenových buněk; Aged; Male; progrese nemoci; Dexamethasone; Maintenance Chemotherapy; thalidomid; lidé; Itálie; Hematopoietic Stem Cell Transplantation; Transplantation, Autologous; Kaplan-Meier Estimate; lidé středního věku; přežití bez známek nemoci; Humans; Disease-Free Survival; Treatment Outcome; Antineoplastic Combined Chemotherapy Protocols; Multiple Myeloma; Middle Aged; Kaplanův-Meierův odhad; melfalan; autologní transplantace; Cyclophosphamide; Czech Republic; protokoly protinádorové kombinované chemoterapie; dexamethason; cyklofosfamid; Austrálie; Time Factors; mnohočetný myelom; rizikové faktory; mužské pohlaví; výsledek terapie; Chemotherapy, Adjuvant; Italy; Proportional Hazards Models; adjuvantní chemoterapie; proporcionální rizikové modely; Prednisone; Disease Progression; prednison; Česká republika; ženské pohlaví; Female; Risk Factors; Melphalan; udržovací chemoterapie